Optimization Techniques for Generic Secure Two-party Computation Platform - Sokhakyan, Tigran V. (Mathematical Problems of Computer Science, 2021)
In this article we present an implementation of general purpose secure twoparty computation framework offering security against semi-honest threat model. Proposed framework implements Yao’s garbled circuits protocol and incorporates novel oblivious transfer protocol based on white-box cryptography methods for the first time to avoid computationally expensive public key operations. Also experimental results illustrating the efficiency of our framework compared with previous implementations are provided.